UJI AKTIVITAS ANALGETIK EKSTRAK ETANOL HERBA SEMBUKAN (Paederia foetida L.) PADA MENCIT PUTIH JANTAN (Mus musculus) YANG DIINDUKSI DENGAN ASAM ASETAT - Triswanto Sentat; Fitri Handayani; Ellen Indraswari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Sembukan plants (Paederia foetida L.) are wild vines that are usually used by people as potential medicinal plants for pain. The purpose of this study was to determine the ethanol extract of sembukan’s herbal analgesic activity in male white mice (Mus musculus) and determine the optimal dose of the ethanol extract from sembukan’s herbal (Paederia foetida L.) which has the potential as an analgesic. Sembukan’s herbal is extracted with 70% ethanol solvent and an analgesic activity test is divided into 5 treatment groups namely positive control group (potassium diclofenac), negative control, dose I (80 mg / kg body weight), dose II (160 mg / kg body weight) ) and dose III (320 mg / kg body weight) by oral administration. Thirty minutes after administration, the mice were given an indicator of pain, 0.5% acetic acid. Analgesic power is calculated by counting the amount of stretching of mice for 1 hour. From the results of the study, the ethanol extract of sembukan’s herbal has analgesic activity in male white mice with percent dose analgesic power 35.18%, dose II 53.58% and dose III 68.98%. The optimal dose that has potential as an analgesic in male white mice is dose III with 68.98% analgesic power.